Penyuluhan Nilai Ekologis dan Peluang Ekspor Produk Pisang Bagi Kelompok Wanita Tani Tunas Hijau Gorontalo - Ardiyanto Saleh Modjo (Yayasan Literasi Sains Indonesia, 2026)
Banana is widely cultivated in Gorontalo; however, its cultivation has declined in West Limboto Subdistrict, while banana leaves and pseudostems (gedebog) remain underutilized despite their ecological and economic potential. Members of the Tunas Hijau Women Farmers Group (KWT) in Hayahaya Village have opportunities to develop banana-based enterprises but have limited knowledge of the environmental functions and export prospects of banana by-products. This community service program aimed to enhance their understanding through an extension activity conducted on 7 May 2026 involving 40 participants. A participatory approach combining presentations and discussions was employed to introduce the ecological roles of banana plants, the export potential of banana leaves, and the utilization of pseudostems for fiber, organic fertilizer, handicrafts, paper, and animal feed. Participants' knowledge was assessed using a rubric and pre-test/post-test instruments. The average score increased from 46.18 before the activity to 85.00 afterward, representing an 84.07% improvement and achieving a Very Good category. These findings indicate that the extension program effectively improved participants' awareness of the environmental and economic value of banana by-products while supporting community empowerment and the development of a self-reliant village through green innovation.